A numerical study on charging of an absorbing sphere in plasmas with different ion compositions. (8th April 2019) - Kiselyov, A A; Krasovsky, V L
Abstract: Results of a direct observation of the charging of spherical bodies in plasmas by means of a numerical experiment are presented. The prime objective of the simulation is to compare quantitative data obtained at different mass ratios of electrons and ions. It is established that the sphere acquires a greater charge at lesser values of the ratio, other things being equal. At high values of the sphere charge, contribution of trapped ions moving in finite orbits near the negatively charged sphere to its shielding by the plasma becomes quite significant. The net charge of the trapped-ion cloud also grows with decrease in the mass ratio as a parameter of the problem in the range of studied plasma parameters.